2022
DOI: 10.31083/j.rcm2305170
|View full text |Cite
|
Sign up to set email alerts
|

Selenoprotein P-1 (SEPP1) as an Early Biomarker of Acute Kidney Injury in Patients Undergoing Cardiopulmonary Bypass

Abstract: Background: Acute Kidney Injury (AKI) is a frequent, dangerous complication in patients undergoing cardiopulmonary bypass (CPB) with oxidative stress playing a crucial role. In this pilot study we evaluated the possible role of the selenoprotein-p1 (SEPP1), a circulating, anti-oxidant selenium transporter, as a predictive biomarker of AKI in this population setting. Methods: Circulating SEPP1 was measured in the blood of 45 patients before surgery and at 4 h, 8 h and 12 h after CPB by Enzyme-Linked Immunosorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In a recent paper, we established SEPP1 as an early and promising biomarker for acute kidney injury in patients undergoing major cardio-surgery operation. SEPP1 increased particularly between the 4th and 8th hours after CPB and with a strict relation with ischemia duration [ 9 ]. In the same paper, we were unable to demonstrate if this plasmatic protein, mainly of hepatic origin, accumulates due to decreased filtration by damaged glomeruli or if renal tubules augment the expression of SEPP1 as a defeat mechanism [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent paper, we established SEPP1 as an early and promising biomarker for acute kidney injury in patients undergoing major cardio-surgery operation. SEPP1 increased particularly between the 4th and 8th hours after CPB and with a strict relation with ischemia duration [ 9 ]. In the same paper, we were unable to demonstrate if this plasmatic protein, mainly of hepatic origin, accumulates due to decreased filtration by damaged glomeruli or if renal tubules augment the expression of SEPP1 as a defeat mechanism [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…SEPP1 increased particularly between the 4th and 8th hours after CPB and with a strict relation with ischemia duration [ 9 ]. In the same paper, we were unable to demonstrate if this plasmatic protein, mainly of hepatic origin, accumulates due to decreased filtration by damaged glomeruli or if renal tubules augment the expression of SEPP1 as a defeat mechanism [ 9 ]. However, in our present experiments, we demonstrated that tubular cells injured by hypoxia indeed upregulate SEPP1 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a pilot research study we recently published, early assessment of selenium P-1 (SEPP1) following cardiopulmonary bypass grafting (CPB) may be very beneficial for enhancing renal risk stratification in patients undergoing heart surgery [4]. Although SEPP 1's existence was initially documented over thirty years ago, the last 10 years have seen many advancements in our understanding of its functions.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, investigation of early biomarkers of acute kidney damage are of increasing interest. In a recent pilot study, Bolignano et al [11] showed that selenoprotein-p1 (SEPP1), a circulating, anti-oxidant selenium transporter, could be a useful predictive biomarker of AKI in patients undergoing CPB. Specifically, circulating SEPP1 release occurs early (at 4 and 8 hours) in patients with AKI; conversely, no difference was noted 12 hours after surgery compared with the control group.…”
mentioning
confidence: 99%